2012
DOI: 10.1016/j.jevs.2012.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Raw and of Cold-Stored Semen in Icelandic Stallions

Abstract: The aim of the present study was to evaluate the quality of raw and cooled semen in Icelandic stallions. Experiments were performed using seven stallions aged between 3 and 19 years. From each stallion, six ejaculates were collected, and semen quality was determined. Thereafter, the semen was split into eight equal parts and processed with and without centrifugation using the extenders INRA 82-egg yolk, INRA 96, GENT, and Equi-Pro to a final concentration of 30 × 106 sperm/mL. The extended semen was then coole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
(21 reference statements)
3
8
0
Order By: Relevance
“…We have demonstrated that the semen characteristics of cold-stored semen were affected by the extender used and the storage time elapsed. Our findings related to ejaculate characteristics of stallions with along sexual rest are consistent with previous studies demonstrating the effect of extender (Webb et al, 2009;LeFrapper et al, 2010) and storage time on stallion semen parameters (Aurich et al, 2007;Janett et al, 2012) when collecting experimental semen samples preceded by repeated semen collection.…”
Section: Discussionsupporting
confidence: 92%
“…We have demonstrated that the semen characteristics of cold-stored semen were affected by the extender used and the storage time elapsed. Our findings related to ejaculate characteristics of stallions with along sexual rest are consistent with previous studies demonstrating the effect of extender (Webb et al, 2009;LeFrapper et al, 2010) and storage time on stallion semen parameters (Aurich et al, 2007;Janett et al, 2012) when collecting experimental semen samples preceded by repeated semen collection.…”
Section: Discussionsupporting
confidence: 92%
“…In our study highest values of PMAI (%) in stored semen were measured in early autumn when ejaculate volume was decreasing. Large and small amounts as well as III IV V VI VII VIII IX X XI XII I II Testosterone concentration (ng/mL) Month of semen collection composition of seminal plasma may impair plasma membrane integrity and motility of coldstored [16,31,32] as well as of cryopreserved semen [14,25]. In addition to the viability also the Ca 2+ content was determined in cold-stored sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Samples of extended semen (30x10 6 spermatozoa/mL) were incubated at 38 °C and analyzed after 10 min. For the measurements a 20 μm deep counting chamber slide (Leja, Nieuw-Vennep, the Netherlands) was loaded with 6 µL of the sample and a minimum of 1000 cells were analyzed in no less than eight randomly selected fields, with 30 frames acquired per field at a frame rate of 60 Hz using standardized settings for stallion semen [16]. Sperm with straightness ≥70% and VAP ≥50 μm/s were considered progressively motile, while sperm with VAP ≥ 50 μm/s were classified as rapid cells.…”
Section: Sperm Motility Assessment With Casamentioning
confidence: 99%
“…Semen was then diluted with INRA 96 TM (IMV technologies, L’Aîgle, France) to a concentration of 30 × 10 6 spermatozoa/ml. Diluted semen was placed in a pre-warmed 20 μm standard count analysis chamber (Standard Count Analysis Chambers SC 20-01-C, Leja, Nieuw-Vennep, The Netherlands) and assessed for motility parameters in 10 fields using a computer-assisted sperm analyser (HTM-IVOS, version 12.1, Hamilton Thorne Biosciences, Beverly, USA) and standardized settings for stallion semen 28 . In each sample, the total motility (%), the average path velocity (VAP μm/s, average velocity of the smoothed cell path), the curvilinear path velocity (VCL μm/s, average velocity measured over the actual point-to-point track followed by the cell), and the straight-line velocity (VSL μm/s, average velocity measured in a straight line from the beginning to the end of track) of sperm cells were determined.…”
Section: Methodsmentioning
confidence: 99%